A Students' Perceptions Group 20 About Competence Lecturer Of Experience Practice (PPL) In PAUD & RA Tunas Qurrata A'yun Garon Village, Balerejo District, Madiun Regency - Mohamad Nasich Jauhari (LP3M STAI MA'ARIF MAGETAN, 2024)
Perceptions of PIAUD Group 20 Students regarding the Competence of Practice Supervisors (PPL) in PAUD and RA Tunas Qurrata 'Ayun in Garon Village, Balerejo District, Madiun Regency. The DPL's ability assessment in accompanying PPL students is expected to be a valid enough reference to determine the level of competency ability possessed by the DPL. The researcher chose this type of research as field research because research on the Perceptions of Group 20 PIAUD Students regarding the competence of PPL field supervisors is not only sufficient with theoretical studies, but requires direct research on those being researched, which is known as observation and uses a systematic approach which is called qualitative. . Based on the findings of research conducted at RA Tunas Qurrata A'yun, Garon Village, Balerejo District, Madiun Regency, it can be concluded that the pedagogical competence of DPL PPL group 20 is good, in accordance with what is stated in law number 14 of 2005 concerning Teachers and Lecturers.